Menciptakan Pengelolaan Kelas Efektif Anak Usia Dini Dengan Gangguan Hiperaktif Dalam Pembelajaran di Taman Kanak-Kanak - Pratama, Anisa; Amelia, Eka; Nur’Aeni, Fitri; Adhwa, Lizia Nurnaya; Wibowo, Naja Aulia; Sabila, Wanda Anggih; Sundari, Nenden (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2025)
This research focuses on identifying and analyzing the effectiveness of classroom management strategies applied in overcoming the difficulties of children with hyperactivity disorder. The purpose is to provide effective and practical strategies for teachers in creating a learning environment that is more conducive and supports the optimal development of children with indications of hyperactivity. This research is a type of descriptive research with a qualitative approach that aims to provide an overview of the problems in children during learning. This research was conducted at Putera II Kindergarten Serang, which is located in Serang District, Serang City, Banten Province. This location was chosen because it was considered relevant to the research objectives, and provided an opportunity to obtain appropriate and actual data. Classroom management is one of the important elements in the learning process that must be carried out by teachers in the classroom because it supports the learning atmosphere to keep it running pleasantly. Thus, classroom management is very important to support the learning process of children, both ordinary children and children with hyperactivity disorders.